Analyzing some main components of MDF-500 disinfectant produced in the United States - Vu Ngoc, Toan; Thi Thu Huong, Nguyen; Nguyen Minh , Tri; Le Hong , Minh; To Phuong , Linh; Dang Thi Ngoc , Chau (Journal of Military Science and Technology, 2025)
The demand for disinfectants has increased exponentially globally following the COVID-19 pandemic to prevent and control the risk of exposure to harmful microorganisms in humans, the environment, and infrastructure. Contaminated surfaces are places where microorganisms can survive for many days. MDF-500 disinfectant has been recommended by the Environmental Protection Agency (EPA) of the USA. MDF-500 disinfectant has a broad spectrum of antibacterial activity against chemical and biological agents. Although widely used, information on the composition of MDF-500 is minimal. Therefore, it is necessary to conduct analytical research to determine the main components of MDF-500 using qualitative and quantitative techniques, as a basis for improving and upgrading technical features. The main components identified include hydrogen peroxide (H2O2), sodium hypochlorite (NaOCl), benzalkonium chloride, cetyltrimethylammonium bromide, and cetylpyridinium chloride. The analysis showed that MDF-500 disinfectant consisted of 1.25% H2O2, 9.47% NaOCl, and pH = 10.74.